Evaluating Career Success: Empirical study on the Objective and Subjective Career Success of Persons with Disabilities in Portugal - Bento, Ana Sofia Matreno (2024)
Dissertação para obtenção de grau de Mestre em Políticas de Desenvolvimento de Recursos Humanos